STRES KERJA: PENYEBAB, DAMPAK DAN SOLUSINYA - Menik Tetha Agustina; Cahya Milia Tirta Safitri (Jurnal Pendidikan Sultan Agung, 2022)
Lecturer is a teaching staff in the university. Lecturers play an important role in the implementation of education, but if the lecturer experiences work stress it will affect his performance. Work stress is the main trigger that will affect the performance of lecturers. Lecturers who do not get social support, work in a less conducive environment, and get a lot of workloads are the main factors causing work stress on lecturers. The impact in carrying out the tridharma of higher education will be hampered, research, community service and education will experience delays. The solution has a good stress coping to be an alternative in dealing with work stress experienced by lecturers.